Malay Islam and Nusantara Islam (Tracking 13 Centuries Of Islam And Malay Synergy For Strengthening Indonesian Indonesia) - Hayatul Islami; Ris’an Rusli; Amilda Sani (The Islamic Education and Multiculturalism Foundation, 2023)
Malay Islam has become an important part of the development of Islam in Indonesia. Various changes in the face of Islam in Indonesia are caused by various interactions from one region to another. This article attempts to trace Malay Islam to build an Indonesian spirit with various other Islamic traditions. This study uses literature studies to analyze genealogically various synergies and relationships between Malay Islam in the local context and Islam in the archipelago nationally. Obtaining data is taken from literature sources that have been published or not yet published, articles, journals, research reports and relevant writings. Data analysis is used with data sorting and data verification stages. This article concludes that the integration of Islam, Malay and the Archipelago has actually built a strong synergy in building a place where both are present, namely the archipelago. On the one hand, the process of Islamization of the archipelago gave confidence and strength to build brotherhood between nations in this archipelago, from Sabang to Meruke.